Succeed with seeds - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2012)
During weekly visits, and supported by their extension agent, a farmer field school in Tanzania learns how to test different sorghum varieties for striga resistance and evaluate how each one performs under different practices.